Bolstering federal execution of EU law: Case C-123/22 Commission v. Hungary (Reception of applicants for international protection II) - Pohjankoski, Pekka (SAGE Publications, 2025)
With the milestone judgment in Case C-123/22 Commission v. Hungary (Reception of applicants for international protection II), the European Court of Justice (‘ECJ’) has bolstered federal execution of EU law. The judgment which imposed a EUR 200 million lump sum and a daily penalty payment of EUR 1 million going forward on Hungary for noncompliance with an earlier ruling demonstrates the ECJ's willingness to impose coercive sanctions with teeth on Member States in cases of particularly serious and persistent infringements. Beyond its practical impact, the judgment is highly significant from the perspectives of the development of the EU's constitutional powers of federal execution, the quasi-automatic enforcement character of the Article 260(2) TFEU procedure, the case law on ‘deliberate’ breaches of EU law, the principle of primacy and judicial conflict, as well as the contentious context of border controls and migrant ‘pushbacks’ in today's Europe.